Depression and Anxiety in Irritable Bowel Syndrome: A Literature Review - A. Deza Farista (HM Publisher, 2022)
Irritable bowel syndrome (IBS) is a common and potential disabling functional gastrointestinal disorder. Studies have revealed a possible association between IBS and psychological problems, such as anxiety and depression. Clinical symptoms of IBS include abdominal pain or discomfort, stool irregularities and bloating, as well as other somatic, visceral and psychiatric comorbidities. Currently, the diagnosis of IBS is based on symptoms and the exclusion of other organic diseases, and therapy includes drug treatment of the predominant symptoms, nutrition and psychotherapy. This review confirms the higher levels of anxiety and depression in patients with IBS; however, no specific subtype has been identified to be associated with higher psychiatric comorbidities compared to the others. The Best Management therapy for reduce anxiety and depression are Low-dose antidepressants and Psychotherapy.